1996
DOI: 10.1055/s-2007-972920
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Ventricular Dimensions and Functions in Athletes and Sedentary Subjects at Rest and During Exercise Using Echocardiography, Doppler Sonography and Radionuclide Ventriculography

Abstract: During recent years the echocardiographic procedure has been extended regarding the evaluation of left ventricular myocardial function during exertion. During exercise echocardiography, body position is important for the correct assessment of cardiac dimensions and function, particularly for the measurement of the cross-sectional diameters of the left ventricle and diastolic myocardial function. Reliable parameters of left ventricular function during exercise are left ventricular ejection fraction and endsysto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 9 publications
2
17
1
2
Order By: Relevance
“…These differences in chamber dimensions were consistently present between the long-distance steeplechasers and all of the other groups of racehorses studied, except for the hurdlers, who run over the same distance range, but over lower, easier fences. As LV chamber width increases in response to dynamic exercise and endurance training in both humans (8,11) and horses (23), these data suggest that conditioned racehorses develop a cardiac morphology that is appropriate to the endurance component of their event. Previous data have also shown that racehorses adapt to commercial training with increases in both wall thickness and chamber width (23), yet we were unable to detect differences in weight-corrected wall thickness in any of the groups in the present study.…”
Section: Discussionmentioning
confidence: 86%
“…These differences in chamber dimensions were consistently present between the long-distance steeplechasers and all of the other groups of racehorses studied, except for the hurdlers, who run over the same distance range, but over lower, easier fences. As LV chamber width increases in response to dynamic exercise and endurance training in both humans (8,11) and horses (23), these data suggest that conditioned racehorses develop a cardiac morphology that is appropriate to the endurance component of their event. Previous data have also shown that racehorses adapt to commercial training with increases in both wall thickness and chamber width (23), yet we were unable to detect differences in weight-corrected wall thickness in any of the groups in the present study.…”
Section: Discussionmentioning
confidence: 86%
“…The physiological adaptations to aerobic training consist of a set of morphological and functional adaptations to metabolism, circulation, and cardiac function [12,13,14,15]. However, the mechanisms responsible for these beneficial effects of exercise training on myocardial remodeling and function after MI remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In older people, it is more difficult to assess the role of hypertrophy. Based on sports cardiologic studies 15,[19][20][21][22][23][24] made in the last few years, the two types of hypertrophy can be best separated functionally, primarily by using the parameters of diastolic function.…”
Section: Introductionmentioning
confidence: 99%